Effects of source and level of supplemental energy on reproductive performance of sows - Christianson, S.; Allee, G.L.; Pollmann, D.S.; Nelssen, Jim L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Three feeding trials utilizing 185 sows (149 primiparous and 36 multiparous) were conducted to evaluate the effects of feeding various levels and sources of supplemental energy during lactation and from weaning to rebreeding on sow reproductive performance. Sows fed tallow (5% or 10%) during lactation had reproductive performance similar to sows fed the basal milo-soybean meal diet. Ad libitum feed intake was not affected by the addition of tallow for either the last week of lactation or for the entire three week lactation. However, daily digestible energy (DE) intake was increased with the addition of tallow to diets. Survival rate of pigs was not significantly affected by adding 5% tallow for the entire lactation period. Adding extra energy (cornstarch or fat) to sow diets following weaning did not improve reproductive performance. However, sows on the higher energy diets tended to show estrus earlier than sows fed the basal diet.
Keywords: Swine; Energy; Reproductive; Performance